2020
DOI: 10.1002/cae.22355
|View full text |Cite
|
Sign up to set email alerts
|

Digital device‐based active learning approach using virtual community classroom during the COVID‐19 pandemic

Abstract: In India, traditional learning approaches in universities follow passive learning and instruction‐based studies. The demand for evidence‐based instructional and interactive active learning processes increases with the advancement in technology. To improve the quality of teaching and student performance, Laureate International University network has taken a unique initiative by applying an iterative and evidence‐based active learning process in small groups at the University of Petroleum and Energy Studies, Deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 26 publications
(33 reference statements)
3
27
0
Order By: Relevance
“…The Discover, Learn, Practice, Collaborate and Assess (DLPCA) is an effective strategy that allows both synchronous and asynchronous sessions, and gives a "whole-class" teaching experience. In [52], this has been experimented with in chemistry courses, and it has its positive impacts on teaching and learning. As blended learning provides provision to conduct group teaching, it has been observed that this reduces the stress and burden of preparing study materials.…”
Section: The Conception Of Blended Learningmentioning
confidence: 99%
“…The Discover, Learn, Practice, Collaborate and Assess (DLPCA) is an effective strategy that allows both synchronous and asynchronous sessions, and gives a "whole-class" teaching experience. In [52], this has been experimented with in chemistry courses, and it has its positive impacts on teaching and learning. As blended learning provides provision to conduct group teaching, it has been observed that this reduces the stress and burden of preparing study materials.…”
Section: The Conception Of Blended Learningmentioning
confidence: 99%
“…Fig. 7 The results of lockdown prediction model for two different scenarios Singhal et al (2020) expounded on how using digital technologies, educational institutions adapted to the COVID lockdown. Their research suggested an iterative and evidence-based active learning process that was able to help students keep up with their studies and showed improved performance and satisfaction rates.…”
Section: Ai and Technologies To Fight Covid-19 Pandemicmentioning
confidence: 99%
“…Active learning is adjusted to the nature, personality, and tendencies of students in the learning activity. Active learning also aims to keep students focus on any given learning activity and actively respond to teacher interactions (Singhal et al, 2020).…”
Section: • Students Lack Supervision (13%)mentioning
confidence: 99%